2020
DOI: 10.2172/1710181
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Floating Offshore Wind Energy in California Between 2019 and 2032

Abstract: We also want to thank the NREL contributors and reviewers, including Eric Lantz, Paul Veers and Brian Smith, as well as Tiffany Byrne, who coordinated the project schedule and deliverables. Technical editing was provided by Deanna Cook and Sheri Anstedt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 24 publications
3
65
0
Order By: Relevance
“…The second novel method is based on machine learning, which has emerged as a promising approach for the vertical extrapolation of wind speeds. Bodini and Optis (2020a) and Bodini and Optis (2020b) explored this concept using four lidars and surface flux stations dispersed around the Southern Great Plains site, operated by Argonne National Laboratory. They found that a relatively simple random forest algorithm, trained on near-surface atmospheric variables, considerably outperformed the conventional power-law and logarithmic wind profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The second novel method is based on machine learning, which has emerged as a promising approach for the vertical extrapolation of wind speeds. Bodini and Optis (2020a) and Bodini and Optis (2020b) explored this concept using four lidars and surface flux stations dispersed around the Southern Great Plains site, operated by Argonne National Laboratory. They found that a relatively simple random forest algorithm, trained on near-surface atmospheric variables, considerably outperformed the conventional power-law and logarithmic wind profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The four vertical extrapolation models presented in the previous section are all validated against lidar data from NYSERDA Buoys E05 and E06 over the full period of record. For each lidar, we consider only the time periods where wind speeds are reported at every height from 20 m to 200 m. Based on recommendations from Section 2, we validate using the REWS calculated from each extrapolation model based on the 10-MW offshore reference wind turbine (Beiter et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…These data sources provide the best means for robust validation of the offshore wind resource, with the ability to assess wind shear and wind veer (i.e., change in wind direction with height) across the entire rotor-swept area of expected 8-to 12-MW offshore turbines and the majority of the 15-MW wind turbines (Beiter et al (2020); Table 5). Furthermore, a growing body of validation exercises are showing strong agreement between lidar-measured and anemometer-measured wind speeds, giving confidence to the exclusive use of floating lidar for offshore wind profile measurements (Carbon Trust 2018).…”
Section: Floating Lidar Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details for calculating REWS are provided in (Wagner et al, 2014). To calculate REWS, we assume a 10-MW offshore reference turbine as described in Beiter et al (2020) and summarized in Table 6. We also assess model performance using the four recommended performance metrics from Optis et al (2020a), summarized 230 in Table 7.…”
Section: Single-column Modelmentioning
confidence: 99%